Genital Pain and Numbness and Female Sexual Dysfunction in Adult Bicyclists. Issue 9 (8th August 2019) - Greenberg, Daniel R.; Khandwala, Yash S.; Breyer, Benjamin N.; Minkow, Roger; Eisenberg, Michael L.
ABSTRACT: Introduction: Bicycle seat pressure on the perineum may impair arousal and clitoral erection, likely contributing to genital pain and numbness experienced by female cyclists. Aim: We aimed to identify the association between genital pain and numbness experienced by female cyclists and female sexual dysfunction (FSD). Methods: Female cyclists were recruited to complete an online survey using the Female Sexual Function Index (FSFI), a validated questionnaire to assess FSD. Cyclist demographics, experience, preferred riding style, use of ergonomic cycle modifications, and genital discomfort while riding were also queried. Multivariate logistic regression analysis was used to evaluate risk factors of FSD. Main Outcome Measures: The main outcome was FSFI score, which is used to diagnose FSD when the FSFI score is <26.55. Results: Of the survey respondents, 178 (53.1%) completed the survey and FSFI questionnaire. Mean age was 48.1 years (±0.8 standard error [SE]), and the average riding experience was 17.1 years (±0.9 SE). Overall, 53.9% of female cyclists had FSD, 58.1% reported genital numbness, and 69.1% reported genital pain. After adjusting for age, body mass index, relationship status, smoking history, comorbidities, and average time spent cycling per week, females who reported experiencing genital numbness half the time or more were more likely to have FSD (adjusted odds ratio [aOR], 6.0; 95% CI, 1.5–23.6; P = .01), especially if localized to the clitoris (aOR, 2.5; 95% CI, 1.2–5.5; P = .02). Females that reported genital pain half the time or more while cycling also were more likely to have FSD (aOR, 3.6; 95% CI, 1.2–11.1; P = .02). Cyclists experiencing genital pain within the first hour of their ride were more likely to have FSD (aOR, 12.6; 95% CI, 2.5–63.1; P = .002). Frequency and duration of cycling were not associated with FSD. Analysis of FSFI domains found that the frequency of numbness was correlated with decreased arousal, orgasm, and satisfaction during intercourse, whereas the frequency of pain significantly reduced arousal, orgasm, and genital lubrication. Clinical Implications: Female cyclists that experience numbness and/or pain have higher odds of reporting FSD. Strengths & Limitations: Our study includes a validated questionnaire to assess FSD and queries specific characteristics and symptoms of genital pain and genital numbness; however, the study is limited by its cross-sectional survey design. Conclusion: This study highlights the need for cyclists to address genital pain and numbness experienced while cycling, and future studies are required to determine if alleviating these symptoms can reduce the impact of cycling on female sexual function.